Control de los ingresos en pandemia en el periodo 2020 y 2021 del Agroservico "Puntoagro" del Cantón Mocache. - Lazo Viteri, Letty Thalya (2022)
The present case study that focuses on the control of income of the Puntoagro agro service of the Mocache Canton, its main activity is the retail and wholesale sale of fertilizers and chemical products for agricultural use, the objective of controlling the income that this had agro service during the pandemic stage, seeks to review the variations that the agro service point agro had during the period 2020 and 2021. Since due to the pandemic (COVID-19), which was the cause that triggered various factors that led to the great decrease in income within the commercial, all this occasionally material and monetary losses that caused it to be unable to meet various obligations in a timely manner. The methodology we used had a mixed approach as a source, showing the descriptive methodology and also the comparison with which it was possible to study and make the proper comparison of income in the periods to be studied. In addition, we were able to closely visualize the work that was carried out in the business through interviews with labor and administrative personnel, and direct observation of the financial statements from which the necessary information was obtained to carry out this case study. The results found were that, although the company had its due planning, where the sales, purchases, and other operations that were carried out in the first year were reflected, the unexpected happened: the pandemic, for which everything baked did not happen. and in the following year, despite the efforts to improve their income, things did not go as expected due to the ravages left by the pandemic.